(untitled) (Siddhajyoti Interdisciplinary Journal, 2023)
Among various school governing bodies, the School Management Committee (SMC) is the leading one that designs the vision and missions for the school. Nepalese education policy has given SMC the duty of school improvement. The theory of governance explains leadership and management quality in its process. So, SMC, from the viewpoint of governance theory, better performs when possesses leadership and management knowledge. This mixed method research explored these qualities in the SMC of Kanchanjunga Secondary School. The qualities are explored from the viewpoints of students and the SMC chair both, where the quantitative data were collected from the students and qualitative from the SMC chair. The research found that the SMC of the researched school possessed less leadership and management qualities. The SMC members need knowledge and training on the traits of leadership and management like decision making and dissemination, setting goals for the school, participatory approach in decision making and implementation, communicative approach, transparency, and accountability